First Finding Of A Male Aphanolaimus Coomansi (Tsalolichin, 1988) In Tropical Areas - Esquivel, Alejandro (1998)
First finding of a male Aphanolaimus coomansi (Tsalolichin, 1988) in tropical ar eas. Nematropica 30:161-166. The rare aquatic nematode Aphanolaimus coomansi Tsalolichin, 1988 was found in some habitats in Costa Rican Conservation Areas, permitting additional taxonomical details to be added to the original description. The first description of a male of the species is also given in this paper. The male’s rele vant characteristics include: 22 pairs of epidermal glands, reproductive system with single posterior reflexed testis, six preanal tuboid supplements and long spicules, gubernaculum weakly cuticularized and tail region provided with well developed setae. A. coomansi is easy to distinguish from other South American species. Some useful diagnostic characteristics are the small body length, few number of body annuli, the origin of the lateral field near the head end and short cephalic setae